Rodzina romska a zdrowie dzieci - Zdulski, Mirosław (Karkonoska Państwowa Szkoła Wyższa, 2011)
The results of research dedicated to Roma families in Central Europe are presented in the article. The results indicate that the condition and health of Roma families are significantly influenced by cultural and social factors. Regardless of the diversity of the Roma culture the traditional concept of health and illness dominates throughout and influences everyday activities related to those issues. The health of entire populations, including children, is determined by their belonging to lower social classes.
Keywords: Roma; family; medicine; health; genetics; culture; lifestyle